Early-onset, conjugal, twin-discordant, and clusters of sporadic ALS: Pathway to discovery of etiology via lifetime exposome research - Spencer, Peter S.; Palmer, Valerie S.; Kisby, Glen E.; Lagrange, Emmeline; Horowitz, B. Zane; Valdes Angues, Raquel; Reis, Jacques; Vernoux, Jean-Paul; Raoul, Cédric; Camu, William (Frontiers in Neuroscience, 2023)
The identity and role of environmental factors in the etiology of sporadic amyotrophic lateral sclerosis (sALS) is poorly understood outside of three former high-incidence foci of Western Pacific ALS and a hotspot of sALS in the French Alps. In both instances, there is a strong association with exposure to genotoxic (hydrazine-related) chemicals years or decades prior to clinical onset of motor neuron disease. In light of this recent understanding, we discuss published geographic clusters of ALS, conjugal cases, single-affected twins, and young-onset cases, not only in relation to their demographic, geographic and environmental characterization but also whether, in theory, there was the possibility of exposure to hydrazine-related chemicals of natural or synthetic origin. Special opportunities to test for such exposures in sALS exist in southeast France, northwest Italy, Finland, the U.S. East North Central States, and in the U.S. Air Force. Given that the degree and timing of exposure to an environmental trigger of ALS may be related to the age at which the disease is expressed, research should best explore the lifetime exposome (from conception to clinical onset) of young sALS cases. Multidisciplinary research of this type may lead to the identification of ALS causation, mechanism, primary prevention, as well as to early detection of impending ALS and pre-clinical treatment to slow development of this fatal neurological disease.